Kue Bangkit Khas Melayu Riau Dari Ubi Jalar Ungu (Ipomoea Batatas L) Sebagai Makanan Fungsional Balita Gizi Kurang - selvi sonia; Imelda Fitri; Sara Herlina (LPPM Universitas Abdurrab, 2023)
ABSTRACT Background: Nutritional problems in toddlers can have serious effects. As a result of these nutritional problems, such as failure to develop physically, less optimal growth and intelligence, can even cause death in toddlers. Objective: To determine the effect of giving rose cakes from purple sweet potato flour as an alternative functional food to malnourished toddlers in the working area the work of the Garuda Health Center, Marpoyan Damai District, Pekanbaru City, Riau. Methods: This study used a quasi-experimental method with a one group pretest-posttest design. This research was conducted in October 2022-July 2023 in the working area of ​​the Garuda Health Center, Marpoyan Damai District, Pekanbaru City. The sample in this study was 18 malnourished toddlers. Results: The results of this study found that the average weight before the intervention was 10.05 kg and the weight after the intervention was 10.93 kg, the difference between weight gain before and after and there was a difference in weight after the intervention was 0.878 kg with a p value = 0.005 and the average nutritional status of toddlers after giving purple sweet potato cake rose was -1.67 with a p value of 0.020 where p <0.05. Conclusion: The conclusion from this study is that there is an effect of giving purple sweet potato rose cakes on body weight and nutritional status of undernourished toddlers in the working area of ​​the Garuda Health Center, Marpoyan Damai District, Pekanbaru City.